Pelatihan Pembuatan Marning Jagung Berbasis Agropreneurship bagi Mahasiswa untuk Optimalisasi Peluang UMKM - Utama, Wigbertus Gaut; Jeramat, Aleksius Arwandi; Tukan, Hendrikus Demon; Dalle, Nautus Stivano (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to equip students with skills in making corn marning and calculate business profits in order to maximize opportunities in Micro, Small and Medium Enterprises (MSMEs) after graduation. This activity was attended by 32 students of the Agronomy Study Program of the Catholic University of Indonesia Santu Paulus Ruteng which was held at the Laboratory of the Faculty of Agriculture and Animal Husbandry (FPP). The activity method used is counseling and demonstration which is divided into three stages, namely Pre-activity, activity implementation, and activity evaluation. The training material includes the analysis of corn marning business opportunities using the SWOT method, the process of making corn marning, and the calculation of the profit of the corn marning business. The results of this service show that there is an increase in the knowledge and skills of students about making corn marning from the initial 40% at the pre-test to 98% when the post-test is carried out. The results of this service show that there is an increase in the knowledge and skills of students about making corn marning from the initial 40% at the pre-test to 98% when the post-test is carried out. This activity produced recommendations to increase student capacity in designing business strategies to enter the world of Micro, Small and Medium Enterprises (MSMEs) with a focus on local agricultural products.